Understanding Goal-Directed Action in Emerging Adulthood: Conceptualization and Method. (February 2016) - Wall, Jessie M.; Law, Ada K.; Zhu, Ma; Munro, David; Parada, Filomena; Young, Richard A.
This article describes an alternative framework for conceptualizing and researching emerging adulthood based on the notions of goal-directed processes. Specifically, contextual action theory (CAT) is proposed to add value to understanding transition-to-adulthood processes because of its emphasis on description, intentional action, and relational context. A related naturalistic, longitudinal method, the action-project method (A-PM), is used to study joint, goal-directed actions and projects (multiple actions over time). The A-PM qualitatively describes joint projects of emerging adults and those involved with them by relying on three perspectives of action: manifest behavior, internal processes, and social meaning. The method consists of video recording joint action between participants, accessing internal processes of action through a video playback interview, and monitoring joint projects over time. This conceptualization and method have been used to describe the joint goal-directed processes inherent in emerging adulthood including parent–youth relationships, friendship, identity formation, and school–work transitions.